1985
DOI: 10.1126/science.3983646
|View full text |Cite
|
Sign up to set email alerts
|

Regenerating Fish Optic Nerves and a Regeneration-Like Response in Injured Optic Nerves of Adult Rabbits

Abstract: Regeneration of fish optic nerve (representing regenerative central nervous system) was accompanied by increased activity of regeneration-triggering factors produced by nonneuronal cells. A graft of regenerating fish optic nerve, or a "wrap-around" implant containing medium conditioned by it, induced a response associated with regeneration in injured optic nerves of adult rabbits (representing a nonregenerative central nervous system). This response was manifested by an increase of general protein synthesis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
35
0

Year Published

1987
1987
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(36 citation statements)
references
References 19 publications
1
35
0
Order By: Relevance
“…Monoclonal antibodies directed against the inhibitory molecules were shown to neutralize the growthinhibitory effect (10). In line with these observations is our finding that the high regenerative capacity of the fish optic nerve is correlated with the presence of a factor or factors cytotoxic to oligodendrocytes (12)(13)(14). This factor(s) was detected among the soluble substances derived from regenerating fish optic nerves, which were collectively termed conditioned medium (CM) and, when applied in vivo, helped to create conditions conducive to axonal growth in other species-e.g., in injured optic nerves of rabbit (15,16).…”
supporting
confidence: 76%
See 1 more Smart Citation
“…Monoclonal antibodies directed against the inhibitory molecules were shown to neutralize the growthinhibitory effect (10). In line with these observations is our finding that the high regenerative capacity of the fish optic nerve is correlated with the presence of a factor or factors cytotoxic to oligodendrocytes (12)(13)(14). This factor(s) was detected among the soluble substances derived from regenerating fish optic nerves, which were collectively termed conditioned medium (CM) and, when applied in vivo, helped to create conditions conducive to axonal growth in other species-e.g., in injured optic nerves of rabbit (15,16).…”
supporting
confidence: 76%
“…Independently, we showed that in vitro this preparation possesses a number of activities, including cytotoxicity to mature oligodendrocytes of both fish and rat (12)(13)(14). The observed correlation between the level of the cytotoxic factor and axonal regeneration in the fish strongly suggested an association between them (14).…”
Section: Discussionmentioning
confidence: 71%
“…Consequently, the cell body fails to reestablish the contact with its end organ and, subsequently, degenerates as well. The posttraumatic degeneration delaying effect of the low energy laser irradiation can be potentially utilized to facilitate regeneration before irreversible degeneration and scarring sets in 21 . This beneficial effect has been exploited successfully in treatments aiming at regeneration' 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Recent observations have offered new clues as to why the adult CNS fails to regenerate (1)(2)(3)(4)(5)(6). It appears that the environment of the injured neuron is involved in determining the ability of the neuron to regenerate after injury.…”
mentioning
confidence: 99%
“…Studies in our laboratory have demonstrated that, in the regenerating optic nerves of fish, there are alterations in the amount of several diffusible polypeptides, the most pronounced being a 28-kDa polypeptide (13), and in the ability of diffusible substances derived from regenerating nerve to trigger a regeneration-like response in a nonregenerative system (2). Regeneration-like activity was induced when diffusible substances were applied around injured optic nerves of adult rabbits, in the form of conditioned medium adsorbed to silicone tubes filled with collagen.…”
mentioning
confidence: 99%